A Comparison of the Syntactic and the Asyntactic Idioms in English - Yahya Mohammed Hussein; Taiseer Flaiyih Hesan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study is theoretically an attempt at identifying the syntax of idioms. It tries to investigate the internal and external syntax of syntactic (and hence SIs) and asyntactic (and hence AIs) idioms in English. This study aims at figuring out the similarities and differences between SIs and AIs in the light of their internal and external syntactic behavior. It is hypothesized that both SIs and AIs could have internal and external syntax. Another hypothesis is that syntax of AIs could be internally fixed, but externally variable. To achieve the aims of this study, the researcher collects many examples of SIs and AIs from many references of English to show their internal and external syntactic behaviour. This research concludes that syntax of SIs and AIs could be internally different, but externally somehow similar in the sense of undergoing external syntactic operations. It is also concluded that the syntactic deviance of AIs can be identified in terms of internal syntax and their internal organization can be to some extent syntactically recognizable.